Influence of conflicting prior information on action anticipation in soccer players: an ERP study - Ji, Qingchun; Zhou, Chenglin; Wang, Yingying (Frontiers in Behavioral Neuroscience, 2023)
This study fits squarely within the scope of Frontiers in Behavioral Neuroscience as the findings reveal neural mechanisms underlying behavioral outcomes. More specifically, this study employs electrophysiological methods, namely, the recording of event-related potentials, to investigate the temporal characteristics of cognitive processing during the anticipation of penalty kick actions by semi-elite soccer players who receive relevant prior information. Innovatively, by pinpointing the time point at which the effect of the prior information was most pronounced through the use of a temporal occlusion paradigm, this research unveiled changes in anticipatory performance and attentional resource allocation in soccer players as they integrated congruent and incongruent prior information and kinematic information. The results showed that at the moment when the prior information effect was maximized, soccer players enhanced early visual attention and conflict monitoring to better integrate both types of information, thereby maintaining higher action anticipation efficiency than non-athletes. The findings provide supporting evidence for the hypotheses put forth in the Model of Information use During Anticipation in Striking Sports.